Ionic Charge-Transfer Liquid Crystals Formed by Alternating Supramolecular Copolymerization of Liquid π-Donors and TCNQ - Iguchi, Hiroaki; Furutani, Hidenori; Kimizuka, Nobuo (Frontiers in Chemistry, 2021)
A new family of liquid π-donors, lipophilic dihydrophenazine (DHP) derivatives, show remarkably high -electron-donor property which undergo alternating supramolecular polymerization with 7,7,8,8-tetracyanoquinodimethane (TCNQ) to form genuine ionic charge-transfer (ICT) complexes. The ICT complexes form distinct columnar liquid crystalline (LC) mesophases with well-defined alternating molecular alignment as demonstrated by UV-Vis-NIR spectra, IR spectra and X-ray diffraction (XRD) patterns. These liquid crystalline ICT complexes display unique phase transition in response to mechanical stress: the columnar ICT phase is converted to macroscopically oriented smectic-like mesophases upon applying shear force. Although there exist reports on the formation of ICT in the crystalline state, this study provides the first rational identification of ICT mesophases based on the spectroscopic data indicating strong electronic interactions between the liquid -donors and solid acceptors. It clearly shows the significance of simultaneous fulfillment of strong π-donating ability and ordered self-assembly of the stable ICT pairs. The flexible, stimuli-responsive structural transformation of the genuine ICT complexes offer a new perspective for designing supramolecular systems with controlled hierarchical self-assembly and electronic structures.